Definitive Insight into the Graphite Oxide Reduction Mechanism by Deuterium Labeling. Issue 9 (26th May 2015) - Jankovský, Ondřej; Šimek, Petr; Luxa, Jan; Sedmidubský, David; Tomandl, Ivo; Macková, Anna; Mikšová, Romana; Malinský, Petr; Pumera, Martin; Sofer, Zdeněk
Abstract The reduction of graphite oxide is one of the most important reactions in the production of graphene in gram quantities. The mechanisms of these widely used reactions are poorly understood. The mechanism of the chemical reduction of two different graphite oxides prepared by the chlorate (Hofmann method) and permanganate methods (Hummers method) has been investigated. Three different reduction agents, lithium tetrahydridoaluminate, sodium tetrahydridoborate, and lithium tetrahydridoborate, as well as their deuterated counterparts, were used for the reduction of graphite oxide. Reduced graphite oxides were analyzed by scanning electron microscopy, energy‐dispersive spectroscopy, elemental combustion analysis, Raman spectroscopy, high‐resolution X‐ray photoelectron spectroscopy, and simultaneous thermal analysis. The concentration of boron incorporated into graphene was measured by prompt gamma activation analysis. Rutherford back‐scattering spectroscopy and elastic recoil detection analysis were used for the determination of the elemental composition, including deuterium concentration, as evidence of CH bond formation.